Organization Development Consulting from Inside Out: A Case Study of Talent Development Program of One Global IT Company - Rattanaphan,Ph.D., Pinyo (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
One of the world's leading IT company based in Thailand was facing challenge both from inside and outside. The most challenging problem was that most of its employees are from IT background. Though they are experts in IT, they lack of soft skills. To develop the company, HRD department designed a series of workshops to train 40 selected talent employees. They were to get training and articulate knowledge to influence influences, with the assistance from OD Consultants from the Organization Development Institute of Assumption University. The project lasted long for four months long. In each month, each participant was to report his or her progress to OD Consultants. Organization Development Interventions Consultants used were Knowledge Management Appreciative Inquiry, Whole Brain Literacy and Dialogue. The results were: there were evidences that most of participants ' soft skills improved. Some participants expanded their influences to larger group of coworkers. Though the project was short, it provided invaluable insight for the OD Consultant. In addition, new models of Appreciative Inquiry, Whole Brain Literacy and Knowledge Management were developed. Key words: Appreciative Inquiry, Whole Brain Literacy, Knowledge Management, Dialogue, the Tipping Point